Optical Cavity Effects in InGaN Micro-Light-Emitting Diodes With Metallic Coating - Hong Chen; Houqiang Fu; Xuanqi Huang; Zhijian Lu; Xiaodong Zhang; Jossue Montes; Yuji Zhao (IEEE Photonics Journal)
We implement finite difference method (FDM) to calculate the optical cavity effects in InGaN micro-light-emitting diodes (LEDs) with metallic coating. The dispersion relation, mode profile, energy density $W$ of electromagnetic field, cavity quality factor $Q$ , and effective mode area $A_{e\,f\,f}$ are theoretically investigated. The results show that although the strongest confinement of the field is achieved by surface plasmon modes at GaN/Ag interface, the energy density $W$ is small inside the cavity, leading to a high effective mode area. Additionally, the cavity without metallic coating has the highest $Q$ factors since no metal loss is involved. These results can serve as guidelines for the design and fabrication of high efficiency and high speed LEDs for the applications of solid-state lighting and visible-light communication.